Substitution of adenine for guanine in the quadruplex-forming human telomere DNA sequence G(3)(T(2)AG(3))(3) - Tomasko, Martin; Vorlícková, Michaela; Sagi, Janos (Biochimie, 2009)
We have studied the formation and structural properties of quadruplexes of the human telomeric DNA sequence G(3)(T(2)AG(3))(3) and related sequences in which each guanine base was replaced by an adenine base. None of these single base substitutions hindered the formation of antiparallel quadruplexes, as shown by circular dichroism, gel electrophoresis, and UV thermal stability measurements in NaCl solutions. Effect of substitution did differ, however, depending on the position of the substituted base. The A-for-G substitution in the middle quartet of the antiparallel basket scaffold led to the most distorted and least stable structures and these sequences preferred to form bimolecular quadruplexes. Unlike G(3)(T(2)AG(3))(3), no structural transitions were observed for the A-containing analogs of G(3)(T(2)AG(3))(3) when sodium ions were replaced by potassium ions. The basic quadruplex topology remained the same for all sequences studied in both salts. As in vivo misincorporation of A for a G in the telomeric sequence is possible and potassium is a physiological salt, these findings may have biological relevance.
Keywords: Circular Dichroism; Guanine; Adenine; DNA; cirkulární dichroismus; G-kvadruplexy; Nucleic Acid Conformation; Telomere; Humans; adenin; sekvence nukleotidů; guanin; Base Sequence; lidé; telomery; G-Quadruplexes; konformace nukleové kyseliny